2004
DOI: 10.1631/jzus.2004.1191
|View full text |Cite
|
Sign up to set email alerts
|

Species-diversified plant cover enhances orchard ecosystem resistance to climatic stress and soil erosion in subtropical hillside

Abstract: Abstract:Naturally occurring plants in agroecosystem evidently play an important role in ecosystem stability. Field studies on the ecological effects of native plants conserved in orchard and their resistance to adverse climatic stress, and soil erosion were conducted from 1998 to 2001 in a newly developed Changshan-huyou (Citrus changshan-huyou Y.B. Chang) orchard. The experimental area covered 150 ha in typical red soil hilly region in southeastern China. The experimental design was a randomized complete blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…High soil water content favours plant growth but plants can have antagonist effects on soil water content. Plants tend to increase soil porosity, which favours water infiltration, and to protect soil from evaporation (Chen et al ., ), overall increasing soil water content, but plants also uptake water reserves and transpire. We showed that in upland rice fields, soil water content was low but increased with weed abundance.…”
Section: Discussionmentioning
confidence: 97%
“…High soil water content favours plant growth but plants can have antagonist effects on soil water content. Plants tend to increase soil porosity, which favours water infiltration, and to protect soil from evaporation (Chen et al ., ), overall increasing soil water content, but plants also uptake water reserves and transpire. We showed that in upland rice fields, soil water content was low but increased with weed abundance.…”
Section: Discussionmentioning
confidence: 97%
“…Among various plant genetics, eugenol is known for its anticancer, antibacterial, sedative, antiinflammatory, anticarcinogenic, neuroprotective, hypolipidemic, and antidiabetic properties [12][13][14]. Eugenol is derived from cinnamon bark, clove buds and leaves, turmeric, pepper, Tulsi leaves, ginger, oregano and thyme.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, multiple ecosystem services depend on the maintenance of weed diversity (Matson et al, 1997;Tscharntke et al, 2005). Diverse plant communities are indicative of the wider sustainability and resistance to stress of the cropping system (Chen et al, 2004;Storkey and Neve, 2018). They provide food sources for biodiversity at higher trophic levels during extended periods (Marshall et al, 2003;Petit et al, 2011;Edesi et al, 2012) and promote large and rich populations of pollinators necessary to the cultivation of arthropod-pollinated crops (Bàrberi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%